Permainan Matematika Online Beads on String untuk Belajar Matematika yang Bermakna dan Menyenangkan di Madrasah Ibtidaiyah (MI) - Hamidah, Dewi; Hakim, Zun Azizul (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2016)
Many people think that mathematics is a scary subject especially among children. Therefore, mathematics should be taught with a good and fun way. One of the good and fun approaches is through games. The development of internet technology has offered a wide range of facility, especially on websites that provide online math games. One of them is free online game âBead on Stringâ. This paper is intended to describe the connection of free online game âBeads on Stringâ, with the materials of the integer division with a remainder and no remainder that is taught at school. The result of the analysis to free online games âBead on Stringâ indicates that the game can be used to build an understanding of learning concepts âPembagian bilangan bulat bersisa dan tak bersisa (Integer division with a remainder and no remainder)â.Ø¸ÙÙ ÙØ«ÙØ± ÙÙ Ø§ÙÙØ§Ø³ Ø£Ù Ø§ÙØ±ÙØ§Ø¶ÙÙØ§Øª Ø¹ÙÙ ØµØ¹Ø¨Ù ÙÙØ®ÙÙØ ÙØ®Ø§ØµØ© Ø§ÙØµØºØ§Ø±. Ø¨ÙØ°Ø§ ÙØ§Ø¨Ø¯ Ø£Ù ÙÙØ¯Ø±ÙØ³ ÙØ°Ø§ Ø§ÙØ¹ÙÙ Ø¨Ø·Ø±ÙÙØ© Ø¬ÙÙØ¯Ø© ÙÙØ±ÙØØ©. ÙØ£ØØ¯ Ø§ÙÙØ¯Ø§Ø®Ù ÙØªØ¯Ø±ÙØ³ ÙØ°Ø§ Ø§ÙØ¹ÙÙ Ø¹Ù Ø·Ø±ÙÙ Ø§ÙØ£ÙØ¹Ø§Ø¨. ÙØ¨ØªØ·ÙÙØ± ØªÙÙÙÙÙØ¬ÙØ§ Ø§ÙØ´Ø¨ÙØ© Ø§ÙØ¯ÙÙÙØ© ØªÙØ¬Ø¯ ÙÙØ§Ù Ø§ÙÙØ³Ø§Ø¦Ù ÙØ®Ø§ØµØ© ÙÙØ¬ÙØ¯Ø© ÙÙ Ø§ÙÙÙØ§ÙØ¹ Ø¹ÙÙ Ø§ÙØ§ÙØªØ±ÙÙØª Ø§ÙÙÙØ¹Ø¯ÙØ© ÙØ£ÙØ¹Ø§Ø¨ Ø§ÙØ±ÙØ§Ø¶ÙÙØ§Øª.Â  ÙÙÙ ÙØ°Ù Ø§ÙØ£ÙØ¹Ø§Ø¨ ÙØ³ÙÙÙ Ø¨ " Bead on Stringâ". ØØ§ÙÙØª ÙØ°Ù Ø§ÙÙÙØ§ÙØ© Ø¹Ø±Ø¶ Ø§ÙØ¹ÙØ§ÙØ© Ø¨ÙÙ ÙØ¹Ø¨ " Bead on Stringâ"Â  Ø£ÙÙ ÙÙÙ Ø§ÙÙØ¬ÙØ§ÙÙ ÙØ¨ÙÙ Ø¹Ø¯Ø¯ ØµØÙØ Ø°Ù Ø¨ÙÙØ© ÙØ¹Ø¯Ø¯ ØµØÙØ ÙÙØ³ ÙÙ Ø¨ÙÙØ© Ø§ÙØªÙ ØªÙØ¯Ø±ÙØ³ ÙÙ Ø§ÙÙØ¯Ø§Ø±Ø³. Ø¯ÙÙØª ÙØªØ§Ø¦Ø¬ Ø§ÙØ¨ØØ« Ø¹ÙÙ Ø£ÙÂ  ÙØ°Ø§ Ø§ÙÙÙØ¹ ÙÙ Ø§ÙÙØ¹Ø¨ ÙÙÙÙÙ Ø§Ø³ØªØ®Ø¯Ø§ÙÙ ÙØ¨ÙØ§Ø¡ Ø§ÙÙÙÙ Ø¹Ù ÙÙÙÙÙ Ø§ÙØªØ¹ÙÙÙ Ø¹Ù " ØªÙØ³ÙÙ Ø§ÙØ¹Ø¯Ø¯ Ø§ÙØµØÙØ Ø°Ù Ø¨ÙÙØ© ÙØ§ÙØ¹Ø¯Ø¯ Ø§ÙØµØÙØ ÙÙØ³ ÙÙ Ø¨ÙÙØ© "